PENINDAKAN ILLEGAL FISHING DAN PERJANJIAN BILATERAL BIDANG PERIKANAN DENGAN NEGARA TETANGGA - Ms. Koesrianti (Fakultas Hukum Universitas Gadjah Mada, 2008)
Indonesia is the biggest maritim state in the world as two third of its area are ocean. In order to maximized its fisheries products, Indonesia has some policies regarding to the management of its waters, including eradicating illegal logging and reforming bilateral agreements with some neighbor countries. This policies, however, appear to be not yet optimal. The government in 1985 has ratified the UN Convention on the Law of the Sea (UNCLOS) 1982 with the Act 17/1985. However, up to now, Indonesia has not ratified yet the United Nations Fish Stocks Agreement 1995 and the 1993 Compliance Agreement as the continued arrangements of UNCLOS 1982. Indonesia should conduct such ratification in order to optimize the Indonesian fisheries industry in which its natural resources, whether living or non-living can be explored and exploited. This is crucial as fisheries industries can provide fish stock as alternative healthy food for the people in Indonesia.